CHARACTERISTIC OF SHALLOW SUBSURFACE LITHOLOGY BASED ON GROUND PROBING RADAR DATA INTERPRETATION AT TEMAJU COAST, SAMBAS DISTRICT, WEST KALIMANTAN PROVINCE - Yogi Noviadi (BULLETIN OF THE MARINE GEOLOGY, 2014)
In order to know the subsurface lithology characteristic at Temaju coast, the Ground Probing Radar (GPR) detection have been carried out. The detection was done along the coast around 11 GPR track line. The equipment which was used are SIR III with 270 MHz antenna. Based on the analysis results of GPR image data which were correlated with the exposed of surface lithology and core drilling log, show that the maximum penetration is about 10 m with the lithology composition as follow: the upper most layer is characterized by sand deposits with about 2 â€“ 3 m width. Below the sand layer is characterized by coral limestone and sandstone. Keywords: subsurface lithology, ground penetrating radar, Temaju Coast Untuk mengetahui karakteristik litologi bawah permukaan di sekitar pantai Temaju, telah dilakukan penditeksian dengan mempergunakan metoda Ground Probing Radar (GPR). Penditeksian telah dilakukan pada sekitar 11 panjang lintasan di sepanjang pantai. Peralatan yang dipergunakan terdiri dari SIR III dengan antenna 270 MHz. Berdasarkan hasil analisis data citra GPR yang dikorelasikan dengan singkapan litologi permukaan dan log pemboran inti, memperlihatkan bahwa penetrasi masimum sekitar 10 m dengan urutan litologi sebagai berikut: lapisan paling atas dicirikan oleh pasir dengan ketebalan sekitar 2-3m. Di bawah lapisan pasir dicirikan oleh batuan gamping terumbu karang dan batu pasir Kata kunci: litologi bawah permukaan, â€œGround Probing Radarâ€, Pantai Temaju